Comparative Study of Reconciliation after Divorce According to the Hanafi Opinion and the Hambali Opinion - Achmad Sulton (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2023)
The number of quarrels in a marriage that causes divorce, due to the unconsciousness of the husband and wife, finally they want to return to the marriage and want to fix their shortcomings with each other. In this study, the author will discuss how rujuk in the view of Madzhab Hanafi and Imam Hambali, and what are the similarities and differences between the two In this study, a type of library research is used, namely research whose object of study uses library data in the form of data source books. Reading, analyzing, and analyzing various existing literature, in this research the author uses a normative approach (juridical normative). The author finds that in Islamic law there are differences of opinion on how to refer to a wife who is referred after the fall of a raj'i divorce (one or two divorces). In the Hanafi Madzhab, the view is that referral is valid if the wife is in the iddah period, whether the referral is by saying sorih (clearly) without intention or in the form of kinayah (innuendo) must be with intention and it is also valid to refer to the wife with actions such as intercourse with intention or not, The Hambali Madzhab is of the view that reconciliation is valid if the wife is still in the iddah period, whether or not he reconciles her with words of sorih (clear) without or with words of kinayah (innuendo) because reconciliation is the cause of making intercourse permissible.